(3GdYdd hGdCYQGV dLGdjfhSs - (3LGdjfhSs
(3ChdgG (B:s
(3bO PcQJ dc ai ZjQ gPg GdebGdI ce eHdZ LejY GdGeQGV GdHSjWI GdeaQOI hGdeQcHI, hbSeJgG CLfGSkG hCfhGYkG , ajfHZi HYO eG JbOe ef Pdc Gf fPcQ CSHGH cd hGMOI efgG s
(3BNQgG (B:s
(3aEf ef QGV faSg aj GdCTjGA GdJj bO hbY YdjgG GdELJeGY hGdeUGOQI , Sgd Ydjg GdCeQ aj EJHGY (B((3EbfGY(B) (3aHdZ GdhLg GdPi Hg jfLh heeG hbY ajg Tc s
(3fSNI QGHYIs
(3JTed Ydi GdebGdI GdKGfjI aj CSHGH GdCeQGVs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B159 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH JjehQ (B95) s
Keywords: (3GdWHs